Analysis of the CSLP Student Loan Defaulter Survey and Client Satisfaction Surveys - Lance Lochner; Todd Stinebrickner; Utku Suleymanoglu (The University of Western Ontario, CIBC Centre for Human Capital and Productivity, 2013)
This analysis confirms our findings from the Defaulter Survey regarding quantitatively important relationships between repayment problems and borrower income. We also identify an important role for student debt, educational attainment, and beliefs about repayment. The analysis further reveals the importance of intergenerational relationships for repayment. Children whose parents are able and willing to financially help them out in times of economic stress are much less likely to experience repayment problems. The extended period of loan designation data associated with the 2010 and 2011 CSS samples allows us to examine the persistence of repayment problems. Individuals who had some form of repayment problem at the date of the CSS (early in their repayment period) were much more likely to be experiencing repayment problems a year or more later than were individuals with no repayment problem as of the CSS. Individuals on IR/RAP were less likely to be experiencing repayment problems 12 and 18 months later than those who were delinquent at CSS; however, both groups had significantly higher serious repayment problems at the later date than did those with no problem at CSS. Our results also suggest that income (at CSS), student loan debt, and educational attainment are important factors affecting default/bankruptcy a year or more after CSS. Interestingly, youth who attended private post-secondary institutions were significantly more likely to experience serious repayment problems 12 and 18 months after CSS.
Keywords: 330